System Architecture and Technology Evolutions in Cloud Radio Access Networks - Shi Yan; Wenbo Wang (Dianxin kexue)
Cloud radio access network（C-RAN）has been proposed as one of the most promising solutions to meet the service requirements of the fifth generation（5G）wireless communication systems. The published achievements indicate that C-RAN has many advantages, which can improve the spectrum efficiency and energy efficiency simultaneously. The state-of-the-art research achievements, system architecture and key technology challenges in C-RAN were studied. Furthermore, the performance gains over the traditional systems were introduced as well.